Comparative evaluation of antimutagenic and antimitotic effects of Morchella esculenta extracts and protocatechuic acid - Stojković, Dejan (2014)
Morchella esculenta (L.) Pers. methanolic extracts, obtained from fruiting bodies growing wild in Serbia and Portugal, were screened for their antimutagenic properties and compared to protocatechuic acid, previously identified in both species. Salmonella typhimurium TA100 reversion assay was used for the antimutagenic properties. Methanolic extracts expressed important antimutagenic potency towards S. typhimurium, which was documented by index of antimutagenicity (I). Sample from Serbia expressed slightly higher antimutagenic properties with inhibition rate of 58.7%. Sample from Portugal gave inhibition rate of 51.7%. Protocatechuic acid had inhibition rate I of his+ revertants of 72.4%. Cell viability in the presence of extracts was also documented. M. esculenta samples from Serbia and Portugal possessed novel biological potential for the studied species, as well as its phenolic compound – protocatechuic acid, identified in both samples. Genotoxic effect, regarding mitotic index and chromosomal aberration score, was also assessed by using Allium cepa L. assay. Protocatechuic acid showed the most significant decrease in mitotic index, as well as decrease in chromosomal aberration score.